Edukasi Permainan Anak Demi Kesehatan dan Ketekunan Beribadah di Kecamatan Kapuas, Sanggau-Kalimantan Barat: Indonesia - Hasahatan Hutahaean; Yeremia Hia; Merina Lilin; Pingkanita Mese Kasse; Jennyus Zai (Jurnal Bangun Abdimas, 2023)
Children's games have been filled with many mobile phone-based games with the android type, where games can be downloaded from the device. Seeing the phenomenon is worth worrying about because it involves many adverse impacts on the eyes, emotional and financial. This community service activity is driven by these familiar situations, both at the city and village levels. Service activities are focused on one of the villages in Rimba Belian, Sei Kodang, Sei Alai, Sanggau, West Kalimantan, with the aim that children no longer spend time in front of gadgets or other computer devices playing games, watching tik-tok, or social media. Activities are carried out by methods with direct field practice with children. Taking examples of games that have existed decades earlier in the country, makes children interested in doing it. Finally, many abandoned the old customs and chose the original game of the archipelago. Thus healthier finances, eyes, and emotions are also more assured